PENANAMAN NILAI KARAKTER REMAJA MELALUI PERMAINAN TRADISIONAL - Ery Wati Nurdiana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
Teenagers are the successor of the nation that we must prepare all their needs both physically and spiritually. Becoming a reliable national successor is not only demanded by high knowledge or extraordinary skills but how to create a successor of the nation of Indonesia with character ?. The cultivation of character nowadays is very important and urgent because the influence of the progress of the globalization era offers many advantages which also have a negative impact. Humans tend to choose to live individually and are more selfish and material. Lack of communication with others will make someone difficult to interact. Cultivation of characters in adolescents can be done through traditional games, this has been done by Misbach (2006) of the Indonesian University of Education entitled